2022
DOI: 10.1073/pnas.2122269119
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic self-caging in active emulsions

Abstract: A common feature of biological self-organization is how active agents communicate with each other or their environment via chemical signaling. Such communications, mediated by self-generated chemical gradients, have consequences for both individual motility strategies and collective migration patterns. Here, in a purely physicochemical system, we use self-propelling droplets as a model for chemically active particles that modify their environment by leaving chemical footprints, which act as chemorepulsive sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Analogous behaviours of 2-D (Hu et al 2019(Hu et al , 2022 and three-dimensional (3-D) isotropic phoretic particles have also been observed (Chen et al 2021;Hu et al 2022;Kailasham & Khair 2022). Besides an isolated unbounded droplet/particle, the effect of nearby boundaries/fluid interfaces (Jin et al 2018;Malgaretti, Popescu & Dietrich 2018;Thutupalli et al 2018;de Blois et al 2019;Lippera et al 2020b;Desai & Michelin 2021;Dey et al 2022;Picella & Michelin 2022), that of an ambient flow (Yariv & Kaynan 2017;Dwivedi et al 2021;Dey et al 2022), and interaction among multiple droplets/particles (Jin, Krüger & Maass 2017;Lippera, Benzaquen & Michelin 2020a;Meredith et al 2020;Nasouri & Golestanian 2020b;Hokmabad et al 2022;Wentworth et al 2022;Yang et al 2023) have been investigated. One specific point that we should mention is that an active droplet/particle near boundaries (Daddi-Moussa-Ider, Vilfan & Golestanian 2022), fluid interfaces (Malgaretti et al 2018) or another droplet/particle (Michelin & Lauga 2015) generally exploits geometric asymmetry to propulsion, which is significantly distinct from an isolated droplet/particle.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Analogous behaviours of 2-D (Hu et al 2019(Hu et al , 2022 and three-dimensional (3-D) isotropic phoretic particles have also been observed (Chen et al 2021;Hu et al 2022;Kailasham & Khair 2022). Besides an isolated unbounded droplet/particle, the effect of nearby boundaries/fluid interfaces (Jin et al 2018;Malgaretti, Popescu & Dietrich 2018;Thutupalli et al 2018;de Blois et al 2019;Lippera et al 2020b;Desai & Michelin 2021;Dey et al 2022;Picella & Michelin 2022), that of an ambient flow (Yariv & Kaynan 2017;Dwivedi et al 2021;Dey et al 2022), and interaction among multiple droplets/particles (Jin, Krüger & Maass 2017;Lippera, Benzaquen & Michelin 2020a;Meredith et al 2020;Nasouri & Golestanian 2020b;Hokmabad et al 2022;Wentworth et al 2022;Yang et al 2023) have been investigated. One specific point that we should mention is that an active droplet/particle near boundaries (Daddi-Moussa-Ider, Vilfan & Golestanian 2022), fluid interfaces (Malgaretti et al 2018) or another droplet/particle (Michelin & Lauga 2015) generally exploits geometric asymmetry to propulsion, which is significantly distinct from an isolated droplet/particle.…”
Section: Introductionmentioning
confidence: 92%
“…that the inertia of both fluid and disk is negligible compared to the viscous force because the Reynolds number Re is typically small in the experiments (Peddireddy et al 2012;Maass et al 2016;de Blois et al 2019;Hokmabad et al 2021Hokmabad et al , 2022Michelin 2023). Hence the fluid flow surrounding the disk can be described approximately by the Stokes equation.…”
Section: Problem Set-up and Governing Equationsmentioning
confidence: 99%
“…Impermeable boundaries like walls will also affect the spreading of inhibitory chemical products and affect the stability of hydrodynamic modes, as recently demonstrated for a droplet near a wall (Desai & Michelin 2021). Experimentally, such inhibitory effects in confinement can immobilise consecutive droplets in an active Bretherton scenario (de Blois et al 2021) or cause reorientation up to self-trapping (Jin et al 2017; Lippera et al 2020 a ; Hokmabad et al 2022 a ).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Surfactant micelles and monomers constitute distinct species that diffuse at significantly different time scales, and these complex kinetics have been found to affect the details of the observed dynamics. Experimental examples include the emergence of bimodal motility through micellar accumulation at hydrodynamic stagnation points (Hokmabad et al 2021), or trail avoidance stemming from chemotactic repulsion by long-lived chemical traces of other droplets (Jin, Krüger & Maass 2017; Moerman et al 2017; Izzet et al 2020; Lippera, Benzaquen & Michelin 2020 a ; Lippera et al 2020 b ; Hokmabad et al 2022 a ). Current analytical and numerical work is looking beyond the one-species approximation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used D as the diffusion coefficient of the surfactant monomer, 31,35 whereas, others have reported D as the diffusion coefficient of the micelles. 11,36 We determine Pe using the experimentally measured average speed of the droplet hvi as the characteristic velocity scale, and the experimentally measured micelle diffusivity, D, using the protocol adopted from Hokmabad et al 37 The droplet phase was doped with a hydrophobic fluorescent dye (Nile Red, Sigma Aldrich) and excited using a laser light of 560 nm wavelength. This facilitates the visualization of the trail of filled micelles released by the droplet during its self-propulsion (see Fig.…”
Section: Motility In Viscous Macromolecular Mediamentioning
confidence: 99%